Acoustic Radiation and Dynamic Study of a Steel Beam Damped with Viscoelastic Material - Liu, Quanmin; Li, Xiaozhen; Xu, Peipei; Liu, Linya; Zhou, Yunlai (KSCE journal of civil engineering, 2020)
Steel structures subject to dynamic loads are prior to generate excessive vibration and noise. Viscoelastic treatment is an effective measure to mitigate the vibration and noise from thin-walled structures in a broad frequency range. H-shaped steel beams are widely used in civil engineering. So an experiment system is established and a series of impact hammer tests are conducted to assess the modal parameters, dynamic response and acoustic behaviour of an H-shaped steel beam coated with various viscoelastic treatments. Firstly, the spectra of the velocity response and acoustic radiation of the bare beam are analysed based on the tested data. Secondly, the resonance frequencies and modal loss factors of the beam with various viscoelastic treatments derived from the frequency response function are compared. Finally, the effect of the layout and thickness of viscoelastic patches on the mitigation of vibration and noise is discussed experimentally. It is shown that the modal loss factor of the first mode increases from 0.012 to 0.191 when the web is treated with 5 mm thick constrained layer damping (CLD). The viscoelastic patches on the web of the H-shaped beam are more effective to control the vibration and noise of the beam than the patches on the flanges. The viscoelastic treatment has distinct effect on the reduction of structural vibration and noise owing to the different dominant frequencies of vibration and noise as well as the frequency-dependent radiation efficiency. The normal velocity level of the H-shaped beam with an 8 mm thick web can be reduced by more than 10 dB and the sound pressure level around the beam about 8 dB when the web is partially covered with the constrained layer damping composed of 2.0 mm thick damping layer and 3.0 mm thick constraining layer.